PENEGAKAN HUKUM PEMERINTAH TERHADAP PELAKU TINDAKAN PUNGUTAN LIAR (PUNGLI) TAHUN 2022 (Studi Kasus Sekolah Menengah Pertama Negeri 4 Pekanbaru) - Zahirsyah, Muhammad; ,, Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study discusses the Government's Law Enforcement Against Perpetrators of Extortion (Pungli) in 2022 which occurred in the environment of SMP 4 Pekanbaru, where the purpose of this study is to determine the Government's Law Enforcement against perpetrators of extortion (pungli) in the educational environment. (Case Study of SMP Negeri 4 Pekanbaru). The research methodology used by the researcher is a qualitative descriptive method. The data obtained from this study will be collected and manifested directly in the form of descriptions or images of the atmosphere or condition of the object as a whole and as it is in the form of spoken or written words from people and observed behavior. The author uses the theory of Sudikno Mertokusumo Theory of Government Law Enforcement which consists of 3 components, namely Legal Certainty (Reechtssichherheit), Benefit (Zweckmaasigkeit) and Justice (gereichtigkeit). Based on the results of the research that has been carried out, it shows that legal certainty in illegal levies carried out by certain SMP 4 Pekanbaru City officials has worked as expected if it receives a report regarding illegal levies that occur. It is certain that such severe sanctions will be imposed, which sanctions that could be given are dismissal from office if it is true that illegal levies are carried out by certain Civil Servant Teachers at SMP 4 Pekanbaru City. The relevant agencies have examined the accused officials directly to avoid unfair punishment if it is not proven, it will be detrimental to the Civil Servants themselves. However, dissatisfaction remains because the reporter feels that he has not been heard regarding the problem of requesting a laptop for follow-up admission at SMP 4 Pekanbaru School. Keywords: Government Law Enforcement, Legal Certainty, Benefit, Justice.